Liberalising Trade in 'Environmental Goods' Some Practical Considerations - Steenblik, Ronald (OECD Trade and Environment Working Papers, 2005)
This chapter explores some practical issues that have arisen in the WTO negotiations on environmental goods and services, especially issues pertaining to liberalising trade in environmental goods. Since environmental goods are not covered by a single chapter of the Harmonized Commodity Description and Coding System (HS) - the international basis for codifying trade and tariffs - an agreement on environmental goods must be defined by reference to an agreed list. In such a case, when the most detailed (6-digit) product level is insufficiently specific, it becomes necessary to agree to create common commodity descriptions at the 8- or 10-digit level in national tariff schedules. Another important concern is the so-called "dual use" problem: many goods with environmental uses also can be used for nonenvironmental purposes. Possible solutions to these problems are explored, drawing on past experience in negotiating and implementing sectoral liberalisation agreements. The chapter also discusses issues relating to separate tariff lines for whole plants and to goods distinguished by their superior environmental performance in use. Finally, it considers some procedural and institutional issues that will have to be addressed before an agreement is concluded, notably whether to allow for the periodic addition of new goods to the agreement, and how to deal with the problem of changes over time in the relative environmental performance of competing goods